Pretreatment of corn cobs using 1-butyl-3-methylimidazolium tetrafluoroborate and dimethyl sulfoxide to enhance enzymatic saccharification - Kuntapa, Manita; Sudaprasert, Kaokanya; Tachaapaikoon, Chakrit (Biomass conversion and biorefinery, 2023)
Ionic liquid (IL) pretreatment is a promising approach for pretreating biomass before converting it into sugars but associated with high costs. The combination of [BMIM]BF 4 : DMSO pretreatment shows the highest delignification, whereas cellulose and hemicellulose recoveries are similar in all pretreatments. The lignin of corn cob pretreated with [BMIM]BF 4 : DMSO has been removed to the amount of1.59- and 1.40-fold of the pretreatment with [EMIM]OAc: DMSO and [BMIM]OAc: DMSO, resulting in a highly porous structure of corn cobs. Furthermore, the delignification of corn cobs pretreated with [BMIM]BF 4 : DMSO can reduce the crystallinity of biomass, regarding a decrease of lateral order index (LOI) and the crystallinity index (CI) of 1.08- and 1.07-fold and 1.04- and 1.03-fold of crystalline cellulose from the pretreatment with [EMIM]OAc: DMSO and [BMIM]OAc: DMSO, respectively. Additionally, the preceding delignification of [BMIM]BF 4 : DMSO pretreatment followed by enzymatic hydrolysis can result in the highest cellulose conversion of 92.98 ± 0.02% when compared with cellulose conversion of [EMIM]OAc: DMSO at 82.84 ± 0.06% and [BMIM]OAc: DMSO at 85.97 ± 0.03%. The combination of using [BMIM]BF 4 featuring DMSO to pretreat lignocellulose biomass is firstly reported in this work.